(3GdLeGfI GdefXheI aj GddZIs - (3GdSjhWj GdNVjQj, CHh GdaVd, LdGd GdOjf, YHO GdQMef Hf CHj HcQ Hf eMeO, J (B911 (3g`s
(3ChdgG (B:s
(3jbhd YHO GdQMef Hf CHj HcQ GdSjhWj GdTGaYj CMeO Gddg MeOG ef ThGFH GdQHgPg ebOeI dWjaI aj GddZIhSejJgG GdLeGfIs
(3BNQgG (B:s
(3YHO GdQMje dfaSg JUjQ ddYhGbH hGfJXQgG aCfJ ef GdYhGbH aj GKfjf JQjMc HGdefi Ch HGdefGjG PGJ GdehJ EMOi GdhGMJjfs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B: 3 / 301s
(3eYLe GdeDdajf(B: 2 / 82s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3GddZIs